Management of recurrent urinary tract infections in women. (March 2022) - Sihra, Néha; Malde, Sachin; Greenwell, Tamsin; Pakzad, Mahreen; Kujawa, Magda; Sinclair, Andrew
Urinary tract infections are highly prevalent and result in significant patient morbidity as well as large financial costs to healthcare systems. Recurrent urinary tract infections can be challenging for many healthcare professionals, and the repeated use of antibiotics in this patient cohort inevitably contributes to the growing issue of antimicrobial resistance and superbugs. It is essential that these patients are appropriately diagnosed and managed to ensure rapid resolution of symptoms and the prevention of chronic or recurrent urinary tract infections. There are several antibiotic-based options available for the prophylaxis of recurrent urinary tract infections however, in the current era of rising antimicrobial resistance, an awareness of antibiotic stewardship and the use of non-antibiotic alternatives for the treatment and prevention of urinary tract infections is of critical importance. We present a case-based multidisciplinary team discussion to highlight how women with recurrent urinary tract infections should be managed, encouraging the use of non-antibiotic prophylactic measures when suitable. Level of evidence: Level 5